2020
DOI: 10.37506/mlu.v20i4.1866
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dual Task Training in Indoor Versus Outdoor Environment on Physical Function and Social Activity among Elderly.

Abstract: The existential reality of elderly is that their physical efficiency is challenged as per their changes in living environment and degree of socialization. Numerous elements of every task performed unconsciously to intervene dual task (cognitive & motor or motor & motor) and so dual task activity training is essential.Aim: To find the influence of dual task activity training in indoor versus outdoor environment on physical activity and social activity self-efficacy measure among elderly. Objectives: a) To study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Characteristics of included studies are presented in Supplementary Table S3. Six of the ten included trials were parallel-group randomized controlled trials [18,20,[27][28][29][30][31][32], whereas three studies were parallel-group controlled trials with no reporting of randomization [19,33,34]. One study was a cluster-randomized, counterbalanced crossover trial [17].…”
Section: Trial Design Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Characteristics of included studies are presented in Supplementary Table S3. Six of the ten included trials were parallel-group randomized controlled trials [18,20,[27][28][29][30][31][32], whereas three studies were parallel-group controlled trials with no reporting of randomization [19,33,34]. One study was a cluster-randomized, counterbalanced crossover trial [17].…”
Section: Trial Design Characteristicsmentioning
confidence: 99%
“…Among the outdoor exercise environments of the 10 included studies, six were not reported in adequate detail (described only as "outdoors", "open", or "large park") [17,19,[32][33][34], two were a mix of natural and built features (i.e., turf field; multisurface garden path) [18,20], and two were mostly natural with minimal built features (i.e., forest; riverside park) [27,28,30,31]. The indoor exercise environments consisted of traditional indoor exercise spaces in three studies (i.e., gym, health club) [18,[27][28][29], laboratory spaces in one study [30,31], university tunnels/skyways in one study [17], and a nursing home hall in one study [20].…”
Section: Exercise Environment: Physical Setting and Conditionsmentioning
confidence: 99%
See 3 more Smart Citations